A Preclinical Candidate Targeting Mycobacterium tuberculosis KasA. Issue 5 (21st May 2020) - Inoyama, Daigo; Awasthi, Divya; Capodagli, Glenn C.; Tsotetsi, Kholiswa; Sukheja, Paridhi; Zimmerman, Matthew; Li, Shao-Gang; Jadhav, Ravindra; Russo, Riccardo; Wang, Xin; Grady, Courtney; Richmann, Todd; et al.
Summary: Published Mycobacterium tuberculosis β-ketoacyl-ACP synthase KasA inhibitors lack sufficient potency and/or pharmacokinetic properties. A structure-based approach was used to optimize existing KasA inhibitor DG167. This afforded indazole JSF-3285 with a 30-fold increase in mouse plasma exposure. Biochemical, genetic, and X-ray studies confirmed JSF-3285 targets KasA. JSF-3285 offers substantial activity in an acute mouse model of infection and in the corresponding chronic infection model, with efficacious reductions in colony-forming units at doses as low as 5 mg/kg once daily orally and improvement of the efficacy of front-line drugs isoniazid or rifampicin. JSF-3285 is a promising preclinical candidate for tuberculosis. Graphical Abstract: Highlights: A structure-based optimization of the KasA inhibitor DG167 led to JSF-3285 The inhibitor evolution focused on metabolic stability and mouse plasma PK JSF-3285 is efficacious in a mouse model of chronic TB infection at 5 mg/kg JSF-3285 represents a preclinical lead compound for TB Abstract : Inoyama et al. disclose the optimization of an indazole antitubercular targeting the β-ketoacyl-ACP synthase KasA. A structure-based approach has overcome significant issues with mouse metabolic stability and pharmacokinetics. A preclinical drug candidate has been delivered with efficacy in a mouse model of chronic M. tuberculosis infection at 5 mg/kg dosing.